The therapeutic results after laparoscopic hellers’ myotomy and partial fundoplication for achalasia - Gülpınar, Kamil; Celasin, Haydar; Sözener, Ulas; Türkcapar, Ahmet (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of this prospectively designed study was to postoperatively assess the subjective complaints or relief of symptoms of achalasia patients’ who underwent Laparoscopic Hellers’ myotomy and partial fundoplication in our clinic. Materials and Methods: 40 patients were enrolled in the study that underwent Laparoscopic Hellers’ myotomy and partial fundoplication (toupet or dor) for idiopathic achalasia in our clinic between years 2002 and 2012. Postoperative follow-up was conducted at 1st, 3rd. and 6th months in each patient for symptoms and a follow-up questionnaire was completed which is classified according to Vantrappen and Hellemans’ modified classification. Results: 34 patients underwent Laparoscopic Heller myotomy with Toupet fundoplication whereas 6 patients underwent Laparoscopic Heller myotomy with Dor fundoplication. After 3 months, 2 patients’ complaints of dysphagia were detected (5%). In the 6 month follow-up, one of these two patient dysphagia symptoms got worsened and a balloon dilatation was performed (2.5%). In the other one no clinical reason was found for dysphagia and medical therapy was initiated. In the 6 th month only three patients (7.5%) were presented with gastroesophageal reflux which successful medical treatment was initiated. Conclusion: Laparoscopic myotomy with fundoplication seems to be the most effective surgical technique that provides both short and long term symptomatic relief with released hospitalization time and less complication rate.